Workload and Compensation Impact on Lecturer Performance - Samsudin, Harun; Rijal, Syamsu; Pranoto, Wati Asriningsih; Rahayu, Puspita Puji; Zarkasi, Zarkasi (Universitas Gajah Putih, 2023)
The goal of Winaya Mukti University, a formal educational institution, is to create excellent human beings. The performance of lecturers, however, is a problem that higher education institutions routinely deal with because it is one of the factors that influences academic progress. Two factors that can affect performance are workload and compensation. The goal of this study is to ascertain, partially or simultaneously, the impact of workload and compensation on the output of professors at Winaya Mukti University. Data were acquired from all of the current topic lecturers. The research included both the descriptive and verification methodologies. In this work, the analysis was performed using multiple linear regression. The results of hypothesis testing show that the workload and pay of course professors at Winaya Mukti University have a positive and significant impact on their performance. Both workload and compensation have a positive and significant effect.